Association of childhood cancer with residential traffic density. - Savitz, DA; Feingold, L (Scandinavian Journal of Work, Environment & Health, 1989)
Data from a recently completed case-referent study of childhood cancer were used to explore a possible role of environmental exposures from traffic exhaust. The street addresses of 328 cancer patients and 262 population-based referents were used to assign traffic density (vehicles per day) as a marker of potential exposure to motor vehicle exhaust. An odds ratio of 1.7 [95% confidence interval (95% CI) 1.0-2.8] was found for the total number of childhood cancers and 2.1 (95% CI 1.1-4.0) for leukemias in a contrast of high and low traffic density addresses (greater than or equal to 500 versus less than 500 vehicles per day). Stronger associations were found with a traffic density cutoff score of greater than or equal to 10,000 vehicles per day, with imprecise odds ratios of 3.1 (95% CI 1.2-8.0) and 4.7 (95% CI 1.6-13.5) for the total number of cancers and leukemias, respectively. Adjustment for suspected risk factors for childhood cancer did not substantially change these results. Though the results are inconclusive, the identified association warrants further evaluation.